Traditional knowledge, medicinal plants, bioactive constituents, and prospecting technology: potential control of fungi (Research, Society and Development, 2021)
The use of plants with medicinal properties for fungi control has led to a continuous exploration of new compounds that could contribute towards promising studies in the development of new drugs and the knowledge of how this control is performed on microorganisms. The objective of this review has been to report on the potential use of medicinal plants to control the pathogenic fungi of a host of plants and animals, which can contribute to the achievement of new formulations for botanical fungicides. Many authors have demonstrated antifungal and general antimicrobial activities for Brazilian flora species through well-established methods, such as by microdilution, agar diffusion, and disk diffusion, while determining a minimum inhibitory concentration (MIC), minimum fungicidal concentrations (MFC), and the inhibition potential of essential oils, extracts and fractions. In this review, 68 species were cited for occurring in Brazil, with 25 being in the north-northeastern part of the country. Thus, most studies about the antimicrobial activities of medicinal plants bring an ‘initial understanding’ of their potential, particularly of some species, genera, and even families. Nevertheless, more data that is exceedingly specific is mandatory by focusing on new and more accurate approaches, such as the action mechanisms, toxicity, the active components, and the verification of the existence of synergic effects. These criteria would be the minimum required to develop new natural products as alternative treatments for the various infectious pathologies that affect plants, animals, and human beings.